The Effectiveness of Group Counseling with Self-Management Techniques to Improve the Student Learning Independence (Jurnal Bimbingan Konseling, 2019)
The purpose of this research was to determine the effectiveness of self-management technique group counseling to improve the learning independence of the junior high school students. The research method is an experiment using the design of one group pre-test and post-test by involving 7 students who have low learning independence as a group members. The results of this research indicate the students' learning independence before being given counseling group self-management techniques, average learning independence of 107.71 (SD = 8.51), then an increase after group counseling was 136.86 (SD 9.02). Paired sample t-test results showed that the self-management technique group counseling was effective to improve the independence of junior high school students (t(6) = 13.743, p < 0.01). This research confirms that group counseling with self-management techniques can be applied to improve student learning independence.